1988
DOI: 10.1016/s0022-5347(17)42857-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of Ureterointestinal Anastomotic Strictures: Comparison of Open Surgical and Endourological Repair

Abstract: The established treatment for ureterointestinal anastomotic strictures is open surgical revision. In an effort to evaluate the efficacy of endourological surgery for this problem, we compared 7 patients (9 strictures) who underwent open revision to 6 patients (7 strictures) who underwent endoscopic incision and balloon dilation of the stricture. The success rate (that is patent ureter and no stent) was 89 per cent for the open revision group and 71 per cent (5 of 7) for the endoscopic group. All open revisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(36 citation statements)
references
References 7 publications
1
29
2
4
Order By: Relevance
“…In order to exclude a local cancer recurrence safely, the biopsy from the affected ureterointestinal area during the open surgical revision seems to be the most reliable method [4, 5]. However, in cases of endourological treatment, imaging methods (CT scans of the abdomen and pelvis) together with endoscopy of the conduit and urinary cytology should be part of the preoperative evaluation of patients with a history of pelvic cancer [11, 22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to exclude a local cancer recurrence safely, the biopsy from the affected ureterointestinal area during the open surgical revision seems to be the most reliable method [4, 5]. However, in cases of endourological treatment, imaging methods (CT scans of the abdomen and pelvis) together with endoscopy of the conduit and urinary cytology should be part of the preoperative evaluation of patients with a history of pelvic cancer [11, 22].…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the morbidity and mortality, the hydronephrosis must be managed preoperatively by a nephrostomy until renal function is restored or sufficiently improved and the infection should be treated efficiently [19]. Kramolowski et al [4]and Vandenbroucke et al [5]reported a high success rate of 89 and 91% with the open surgical revision, respectively. However, this success was related to considerable morbidity, longer hospital stay and therefore higher hospital costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open surgical revision remains the treatment of choice with a success rate of around 80% [3]. However, the difficulty due to extensive intra-abdominal adhesions, the significant operative and post-operative morbidity (vascular injury, wound infection) [4,5] leads to look for less invasive procedure with shorter hospital stay, especially that the patients are generally old with concomitant morbidity. Alternative options include endoscopic techniques such as balloon dilatation, endoscopic incision, stricture stenting, and endoscopic stricture incision combined with balloon dilatation.…”
Section: Introductionmentioning
confidence: 99%
“…If successful, these procedures can spare patients the nuisance of chronic indwelling stents which usua11y carry an increasing rate of complications (e.g., infection, stone formation, stent encrustation, etc.) or the risk of repeated operation which is often technically difficult (2).…”
Section: Introductionmentioning
confidence: 99%